IMPLEMENTASI METODE PROTOTYPE PADA WEB MULTIMEDIA UNTUK MEDIA PROMOSI DIGITAL PADA MELY FLORIST - Putri Nabila Zahra; Supiyandi; Ricky Ramadhan Harahap (CV. Hawari, 2026)
In the digital era, the use of information technology has become a major need in supporting business activities, including in the micro, small, and medium enterprises (MSMEs) sector to be more digitally literate in order to compete in the business world. Mely Florist is an MSME engaged in the sale of flower boards. Small businesses such as Mely Florists or what we often call a local florist face the challenge of competing through effective and innovative promotions. Digital promotional media (such as websites and social media) are key to reaching potential customers. However, for now, the profile website owned by mely florist does not support the optimization of information management effectively. The method used is a prototype with a final result in the form of a web-based system that supports product management and ordering. The implementation of this system is expected to increase operational effectiveness, as well as support Mely Florist's digital marketing strategy more optimally. The prototype method is used because it is a flexible, efficient, and user-centric way to develop products and can help manage uncertainty. It can also produce products that are more in line with the needs of the market and users. Multimedia web as a promotional medium for mely florists uses the creation of an interactive initial prototype, involving iterative user input to improve the vitur such as flower product galleries, visual animations, promotional media elements. Mely florist also needs an attractive digital platform to promote florist products effectively in the digital era